An Electrochemical Biosensor Based on NiO Nanoflowers/Polymethylene Blue Composite for Non-Enzymatic Glucose Detection. Issue 14 (11th November 2020) - Zhu, Luyi; Wei, Zhenbo; Wang, Jun; Zhong, Jianli
Abstract : It is of great importance to determine the quantification of glucose in human serum. In this work, a novel NiO nanoflower/polymethylene blue (NiO/PMB) modified glassy carbon electrode (GCE) was fabricated and taken as a non-enzymatic glucose biosensor. The composite was characterized by field-emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD). The electrochemical properties of the modified biosensor were investigated by the cyclic voltammetry (CV) method. This biosensor combined the advantages of NiO nanoflower and PMB, so that a series of characterization results indicated that the composite material exhibiting satisfactory catalytic activity towards glucose. The quantitative determination of glucose was carried out by chronoamperometric measurements (i–t) method and showed linear ranges between 3−50 μ M and 50−80 μ M, with the limit of detection (LOD) of 2 × 10 −7 M (S/N = 3). Under optimal conditions, the sensitivity of the self-assemble biosensor was calculated to be 413.06 μ A cm −2 mM −1 for glucose. The selectivity, reproducibility, and stability of the glucose biosensor were also confirmed in the study. In addition, this glucose biosensor was successfully applied for the analysis of glucose in real human serum samples.